Perancangan User Interface dan User Experience Pada Website Employee Benefit PasarPolis Menggunakan Metode Design Thinking - Panji Dharmawan; Nurul Adha Oktarini Saputri (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
PasarPolis is the first online insurance company in Indonesia established in 2014. The company aims to be the best insurance provider in Indonesia by providing easy access, fast service, and affordable prices. Pasar Polis provides various types of insurance, including health insurance, life insurance, accident insurance, travel insurance, and car insurance. In addition, PasarPolis also has an employee benefits program, providing insurance solutions for companies and employees. This program offers benefits for companies, such as providing insurance protection and employee benefits, as well as employee retention and company loyalty. One of the ways used by companies to inform their employees about the Employee Benefit program is through the PasarPolis Employee Benefit website. However, the PasarPolis website is not user-friendly, making it difficult for employees to find information and access Pasarpolis Employee Benefit services efficiently. Therefore, it is necessary to redesign the user interface and user experience of the PasarPolis Employee Benefits website to make it easier to use and easier for company employees. Design thinking is a design methodology that emphasizes empathy for users and creative problem solving. This approach includes stages such as empathy, definition, ideation, prototyping, and testing to help develop innovative solutions based on user needs. By using the Design Thinking approach, the UI and UX design of the Pasarpolis Employee Welfare website can be improved to meet user needs. The interim results of this research include various UI and UX designs generated through prototyping. These prototypes have been tested with users to obtain valuable feedback. The results of this testing helped the team in improving the designs and steering the design towards a better user experience. This research contributes to the improvement of the Pasarpolis Employee Benefit website through a Design Thinking approach that focuses on a deep understanding of user needs and design iterations based on user feedback. Thus, it is expected that these interim results can improve the quality of UI and UX on the website